LPS pretreated dental follicle stem cell derived exosomes promote periodontal tissue regeneration via miR-184 and PPARα-Akt-JNK signaling pathway - Liangrui Chen; Jiaxiang Zhang; Jialu Yu; Shujuan Guo; Weidong Tian (Stem Cell Research & Therapy)
Abstract Purpose Lipopolysaccharide (LPS) pretreated dental follicle stem cells (DFSCs)-derived exosomes (L-D-Exo) exhibit enhanced therapeutic effects in periodontitis treatment, but the effective components responsible for these effects remain unidentified. The aim of this study is to investigate the differences in expression profile and regulatory effect of the exosomal microRNAs (miRNAs) from DFSCs and PDLSCs on periodontal tissue regeneration. Methods High-throughput miRNA sequencing was performed on DFSCs and PDLSCs derived exosomes under both Porphyromonas gingivalis (P.g) LPS pretreatment and normal conditions. Through bioinformatic analysis, miR-184 was selected as the key miRNA due to its specific down-regulation in L-D-Exo, which linked to oxidative stress regulation. After changing the expression of miR-184 in PDLSCs, the fluorescence intensity of reactive oxygen species (ROS), malondialdehyde (MDA) content and antioxidant related enzyme activities, and the expression levels of inflammatory cytokines and osteogenesis-related genes in PDLSCs were detected. In addition, dual-luciferase reporter assay and Western blot were used to explore the target gene and downstream signaling pathways. In vivo, miR-184 Antagomir was injected into mice with experimental periodontitis to evaluate the role and mechanism of miR-184 in periodontal tissue regeneration. Results Inhibition of miR-184 in PDLSCs significantly impaired oxidative stress, as evidenced by decreased ROS fluorescence intensity and MDA content, alongside increased activities of antioxidant enzymes. This reduction in oxidative stress subsequently decreased the expression of intracellular inflammatory cytokines, while promoting the expression of osteogenic genes. The dual-luciferase reporter assay confirmed the direct binding of miR-184 with Peroxisome proliferator-activated receptor α (PPARα). MiR-184 inhibition activated the downstream protein kinase B (Akt) pathway and inhibited the c-Jun N-terminal kinase (JNK) pathway under inflammatory conditions. Furthermore, miR-184 Antagomir application also enhanced the therapeutic efficacy of periodontitis mice by reducing inflammation and promoting periodontal osteogenesis. Conclusion Inhibition of miR-184 facilitates periodontal regeneration, which targets the PPARα-Akt-JNK signaling pathway to suppress oxidative stress in periodontal tissues.